The Implementation Of Maintenance Works For Historical Buildings – A Review On The Current Scenario - Abdul Rashid, Robiah; Ahmad, A. Ghafar (2008)

(untitled)
The conservation of historical buildings is a method on preserving structures which are historically and culturally important to the nation.